(3GdJWhQ hGbJUGOjGJ GdehGQO (B:s (3OQGSI NGUI HJWhQ GdacQ hGdhbGFY GdEbJUGOjI hGbJUGOjGJ ehGQO YfGUQ GdEfJGL (B/s - (3Jhajb, eMH NdIs ((3GdEScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2011)
(3JWhQ GdacQ hGdhbGFY GdEbJUGOjI(B- (3GdGfXeI GdEbJUGOjI aj GdYUhQ GdbOjeI hGdhSWi(B- (3GdfXe GdEbJUGOjI aj GdYUQ GdMOjK(B- (3GbJUGOjGJ GdehGQO GdWHjYjI(B- (3GdJYQja HGbJUGOjGJ GdehGQO hJbSjeGJgG hNUGFUgG(B- (3GdehGQO GdWHjYjI, Gdeaghe, GdcaGjI hGdGfhGY(B- (3GdGHYGO GdEbJUGOjI ddehGQO GdWHjYjI(B- (3Cge GdeTcdGJ GdEbJUGOjI GdcdjI GdeQJHWI HGdehGQO GdWHjYjI (B- (3GbJUGOjGJ GdehGQO ZjQ GdWHjYjI(B- (3GbJUGOjGJ GdehGQO GdHTQjI(B- (3Cge GdeTcdGJ GdEbJUGOjI GdcdjI GdeQJHWI HGdehGQO GdHTQjI(B- (3GbJUGOjGJ ehGQO GdJfXjes
(3GdeQGLY U(B.431s
Keywords: (3GdCfXeI GdEbJUGOjIs; (3GdJWhQ GdEbJUGOjs; (3GdacQ GdEbJUGOjs